Third V.T. Krishnamachari Memorial Lecture 1986 - Planning Commission (Planning Commission, 1987)
I am deeply grateful to the Institute of Economic Growth for the honour they have conferred on me by inviting me to deliver the Sri V.T. Krishnamachari Memorial Lecture. I am moved all the more as I am called upon to follow two of the greatest Indian economists of two different generations Dr. V.K.R.V. Rao and Dr. K. M. Raj, a task, I am afraid, much beyond me. I crave your indulgence for the failures and shortcomings that you may discover.
Institute of Economic Growth
Institute of Economic Growth